An alternative in menses management - Joana Correia Rodrigues; Sara João Branco Cardoso (Instituto Politécnico de Viseu, 2021)
Introduction: The menstrual cup (MC) is a menses management alternative, being little known. This study objective was to discover if Lisbon School of Medicine (FMUL) medical students know the MC. Objective: The main objective of this study was to verify whether the medical students of the Faculty of Medicine of Lisbon (FMUL) know the MC well. Methods: In the study first phase, a bibliographic review was made and a questionnaire was structured and tested in a pilot population. The second phase started after the Ethics Committee approval and consisted on giving the questionnaire to all FMUL medical students. Results: Of the 2169 students who received the questionnaire, there were obtained 970 responses. The majority of participants knew of the MC (93.8%), mainly from social networks, friends and social media and less frequently from family, lessons, workshops/conferences and doctor. Most of them were familiar with MC functions, although there were misconceptions. Of the 755 women, 108 already used the MC, being more recently used. Most women (39.6%) considered its use, being the most susceptible the ones with average-heavy menstrual flow and those who used tampons. Conclusion: Although FMUL medical students heard about the MC, there is a lack of knowledge of all its potentialities. So, it is required to provide information about it in academic/scientific events and healthcare-centers. Finally, there should be a bigger investment in the medical curriculum regarding menses management.